PENGARUH HUKUM INTERNASIONAL TERHADAP PERKEMBANGAN HUKUM NASIONAL - Putu Gita Sunia Sari (Universitas Pendidikan Ganesha, 2022)
International law is a body of law that is mainly composed of principles, which are standards of behavior that a state requires and therefore follows and adheres to in interactions between these states. The main sources of international law are international treaties, namely bilateral agreements (made by two countries) and multilateral agreements or conventions (made by more than two countries) (especially contract slavery). The Indonesian government is forced to enact laws containing customary rules in treaties that have not been ratified, which is contrary to national law. With the existence of international law (particularly indentured servitude), the Indonesian government is compelled to issue laws whose substance contains customary rules in treaties that have not been ratified. That international law influences the development of national law becomes the basis for solving the problem of whether international law affects the development of national law.